(untitled) (Acta Scientiarum. Health Sciences, 2023)
Interprofessional Education is characterized by a set of collaborative actions, developed by different professionals, from the exchange of knowledge and professional development in the educational sphere. The aim of this study was to explore the initiatives and possibilities of interprofessional education in health courses. This is a descriptive and exploratory research, with a qualitative approach, in which the data were absorbed from the Pedagogical Projects of the Courses (PPCs) of undergraduate health of a Federal University and the experiences of 14 academics, 4 coordinators and 6 professors. In the data collection, we used semi-structured interviews and documental analysis of the PPCs of the courses, analyzed through content analysis. Thematic units were identified as: “Curricular initiatives of interprofessional education in health courses”, “Initiatives of interprofessional education in health courses according to the academic community” and “Possibilities of interprofessional education in health from the perspective of the academic community”. The results indicated the absence of IPE in the health courses investigated with few curricular initiatives that ensure a training directed to the interprofessional competencies required by the UHS.